Social structure and distribution of guanaco (Lama guanicoe cacsilensis) in the Calipuy National Reserve, Peru. - Linares, Luis (2010)
The objective of this research was to study the distribution and social structure of the guanaco in the Calipuy National Reserve (RNC), La Libertad, Peru. 430 guanacos were reported with a slight downward trend (b = - 10.21), distributed in 114 km2. The adults were most numerous with 73.5% ± 9.8 (p<0.01) followed by juveniles and chulengos 16.1% ± 3.93 y 10.4 ± 5.9 respectively. The 72% of the population was found in family groups, 18% in herds and solitary accounted for 10%. The density was 5.7 individuals per km2. The population was mostly concentrated in the north, above 3000 m (p <0. 01), which is also the most heavily fortified, reaching 18.9 ± 8.97 guanacos/km2 and family groups mainly houses. The western zone under 3000 m and closer to the breeding area, was the lowest density 0.24 ± 0.24 guanacos/km2, and maintained primarily solitary and groups of males.